2019
DOI: 10.1111/all.13954
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐13: Targeting an underestimated cytokine in atopic dermatitis

Abstract: Atopic dermatitis (AD) is a common inflammatory skin condition that has traditionally been considered a paradigmatic type 2 immunity (T2)-driven disease. Interleukin (IL)-4 and IL-13 are both pivotal cytokines involved in the generation of allergic diseases. Currently, besides dupilumab, which blocks the binding of both cytokines to their receptors, a number of new pharmacologic entities have been designed to target both T2 cytokines and/or their receptors and/or receptor-associated signal transduction machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
273
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(319 citation statements)
references
References 104 publications
8
273
1
12
Order By: Relevance
“…IL-13 binds 13R 1 which complexes with IL-4R to form the type 1 receptor signaling, but IL-13 also binds the cell surface and soluble forms of the monomeric type 2 receptor (IL-13R 2 chain). However, IL-13R 2 has a decoy effect, lacking signal transduction machinery and limiting the activity of IL-13 since binds the cytokine making it unavailable for activating type 1 receptor [36][37][38][39]. Herein, we have shown that rIL-13R 2 chain limits the ability of mice to respond to E. caproni primary infection, even in the presence of rIL-25.…”
Section: Discussionmentioning
confidence: 79%
“…IL-13 binds 13R 1 which complexes with IL-4R to form the type 1 receptor signaling, but IL-13 also binds the cell surface and soluble forms of the monomeric type 2 receptor (IL-13R 2 chain). However, IL-13R 2 has a decoy effect, lacking signal transduction machinery and limiting the activity of IL-13 since binds the cytokine making it unavailable for activating type 1 receptor [36][37][38][39]. Herein, we have shown that rIL-13R 2 chain limits the ability of mice to respond to E. caproni primary infection, even in the presence of rIL-25.…”
Section: Discussionmentioning
confidence: 79%
“…IL-13 binds 13R1 which complexes with IL-4R to form the type 1 receptor signaling, but IL-13 also binds the cell surface and soluble forms of the monomeric type 2 receptor (IL-13R2 chain). However, IL-13R2 has a decoy effect, lacking signal transduction machinery and limiting the activity of IL-13 since binds the cytokine making it unavailable for activating type 1 receptor[37][38][39][40].…”
mentioning
confidence: 99%
“…Atopy is a genetic predisposition to develop allergic symptoms caused by environmental antigens (allergens). Numerous studies indicate that two of the key cytokines are interleukin-4 (IL-4) and IL-13 [1,3]. They are potent mediators of the induction and effector phases of the Th-2 immune response.…”
mentioning
confidence: 99%
“…Early studies strongly suggested that AD is also linked to Innate lymphoid cells2 (ILC2) dysregulation. ILC2 express pro-allergic mediators IL-4, IL-5, IL-9, IL-13 [1,16]. It was proved that in comparison to CD4+, ILC2 are capable of producing IL-5 and IL-13 cytokines per-cell in case of allergic inflammation against house dust-mite independently.…”
mentioning
confidence: 99%
See 1 more Smart Citation